Probability of Heritage Language Use at a Supportive Early Childhood Setting in Australia - Escudero, Paola; Jones Diaz, Criss; Hajek, John; Wigglesworth, Gillian; Smit, Eline Adrianne (Frontiers in Education, 2020)
Despite well-established research that documents the intellectual, linguistic, sociocultural and familiar benefits of early childhood bilingualism, Australia’s provision of heritage language (HL) support in early childhood (EC) settings is fairly minimal, resulting in little to no access to the HL outside of the home. We report on language data from a long day care preschool that has an open bilingual policy, where two languages (HL and English) are used in naturalistic interactions between children and educators. While the quantity of language input and output is known to impact on language proficiency, there are no prior studies which focus on establishing the quantitative nature of naturalistic language production in a bilingual preschool. Our goal was to document the relative language input and output of HL and English and to examine whether there are differences across age groups in the EC setting, and during different activity types. We followed a quantitative approach in data collection and analysis, with child and educator observations over a period of eight weeks and an analysis of targeted videos amounting to close to an hour of recordings per child. We used Bayesian modelling to test the probability of HL use in the different age groups and per activity type. Overall, HL input was higher for toddlers than preschoolers and toddlers received more HL input than English, while preschoolers received comparable input in both languages. The higher probability of HL input in toddlers was particularly in evidence during story time and playing activities. Our results indicate a high level of HL use in this EC setting, suggesting success in HL maintenance and promotion of early bilingualism. Further research should explore the children’s relative language output in relation to their input, individual differences, as well as extending the current methodology to other similar settings in Australia.